Description of an activity-based enzyme biosensor for lung cancer detection - Dempsey, Paul W.; Sandu, Cristina-Mihaela; Gonzalezirias, Ricardo; Hantula, Spencer; Covarrubias-Zambrano, Obdulia; Bossmann, Stefan H.; Nagji, Alykhan S.; Veeramachaneni, Nirmal K.; Ermerak, Nezih O.; Kocakaya, Derya; Lacin, Tunc; Yildizeli, Bedrittin; et al. (Communications medicine, 2024)
Background Lung cancer is associated with the greatest cancer mortality as it typically presents with incurable distributed disease. Biomarkers relevant to risk assessment for the detection of lung cancer continue to be a challenge because they are often not detectable during the asymptomatic curable stage of the disease. A solution to population-scale testing for lung cancer will require a combination of performance, scalability, cost-effectiveness, and simplicity. Methods One solution is to measure the activity of serum available enzymes that contribute to the transformation process rather than counting biomarkers. Protease enzymes modify the environment during tumor growth and present an attractive target for detection. An activity based sensor platform sensitive to active protease enzymes is presented. A panel of 18 sensors was used to measure 750 sera samples from participants at increased risk for lung cancer with or without the disease. Results A machine learning approach is applied to generate algorithms that detect 90% of cancer patients overall with a specificity of 82% including 90% sensitivity in Stage I when disease intervention is most effective and detection more challenging. Conclusion This approach is promising as a scalable, clinically useful platform to help detect patients who have lung cancer using a simple blood sample. The performance and cost profile is being pursued in studies as a platform for population wide screening. Plain language summary Lung cancer is responsible for more deaths worldwide than all other cancers. It is often detected with the appearance of symptoms when treatment is limited and outcomes for the patient are much worse. While imaging chest scans can detect disease, they are poorly used even in the United States where it is an approved screening method. When cancer is present, protease enzymes are responsible for making space and modifying the lung tissue for the growing tumor. This report describes a panel of 18 sensors that release a fluorescent signal when these enzymes are present in a blood sample. The signal acts like a fingerprint of activity that can be used to identify people with lung cancer. This sensor platform can detect patients with curable lung cancer and could provide a platform for screening very large populations of at-risk individuals. Dempsey et al. present a graphene-based biosensor technology to detect enzyme activity in serum samples. A model is developed based on the activity of a panel of these biosensors to classify 90% of patients with lung cancer across all stages of disease, providing a potentially useful screening technology.